Perception and acceptance of traditional Bugis food in Parit Raja - Zakariah, Siti Hajar; Ahmad, Nor Aziah; Md Sabron, Nurdiyana (Penerbit UTHM, 2021)
Malaysia is a multiracial country comprising Malay, Chinese, Indian, Iban, Kadazan, Javanese, Bugis and many others. According to (Jamaludin & Ramli, 2018), the uniqueness of a plural society can be describe not only involving a multi-racial society. It is also color with a society of different beliefs and religions as well as different cultures. The transfer of a race occurs because it has its own history of how the entry of a certain race took place in this country. The transfer of a race occurs because it has its own history of how the entry of a certain race took place in this country. Bugis are a well- known ethnic in Indonesia from the archipelago of Sulawesi or Celebus island, which has an average population of three million people living in the southern part of the Sulawesi archipelago, (Ammarell, 2002). Bugis migration to Malaya, especially in Sabah, Selangor and Johor had long accepted.